Al-Cu alloy capable of simultaneously improving room temperature performance and high temperature performance and preparation method of Al-Cu alloy

By introducing Z and Q elements into the Al-Cu alloy, Al3Z heterogeneous core and Cu-Q-vacancies are formed, the problem of degradation of Al-Cu alloy at high temperatures is solved, and the effect of simultaneously improving room temperature and high temperature performance is achieved.

CN119553155APending Publication Date: 2025-03-04NORTHWESTERN POLYTECHNICAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411790675.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

Al-Cu alloy has deteriorated performance in high-temperature environments, making it difficult to meet the requirements of room temperature and high-temperature performance at the same time.

Method used

By introducing Z (Sc or Zr) elements to form Al3Z heterocores and refine grains; at the same time, Q (Sn, Cd or In) elements are introduced to promote the formation of Cu-Q-vacity clusters during the aging stage, and enhance the precipitation and distribution uniformity of the θ'-Al2Cu phase.

Benefits of technology

It effectively improves the room temperature performance of the alloy and significantly enhances the high temperature performance, maintaining stability at high temperatures through the "sequential thermal stabilization" effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119553155A_ABST
    Figure CN119553155A_ABST
Patent Text Reader

Abstract

The invention provides an Al-Cu alloy capable of simultaneously improving room temperature performance and high temperature performance and a preparation method of the Al-Cu alloy, and belongs to the technical field of aluminum-copper alloys. According to the method, Z (Z is Sc or / and Zr) elements are introduced to form Al3Z heterogeneous core refined grains, Q (Q is Sn, Cd or In) elements are used for promoting formation of Cu-Q-vacancy clusters, and the size, distribution uniformity and precipitation number density of a theta '-Al2Cu phase are regulated and controlled. The synergistic effect of the two remarkably improves the room temperature and high-temperature performance of the alloy at the initial stage of thermal exposure. The element Q promotes formation of X (X is Cr, Mn or Cr and Mn)-Cu-vacancy clusters in the aging process, and enrichment of the element X in a theta '-Al2Cu phase is improved; and the X element is segregated on an interface and participates in a solute partition effect, so that the thermal stability is further enhanced. And in the later stage of thermal exposure, X and Z are diffused to coherent and semi-coherent interfaces of the theta '-Al2Cu phase respectively, the coarsening driving force is reduced, solute dragging is generated, the size increase of the precipitated phase is inhibited, and therefore the sequential thermal stabilization effect is formed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of aluminum alloy manufacturing, and in particular relates to an Al-Cu alloy capable of simultaneously improving room temperature and high temperature performance and a preparation method thereof. Background Art

[0002] Al-Cu alloy is a typical precipitation-strengthened aluminum alloy, and its strengthening mainly depends on the high number density and high aspect ratio θ'-Al2Cu phase formed during the aging process. However, when the ambient temperature is greater than 200°C, the θ'-Al2Cu phase will undergo Ostwald ripening, which significantly reduces its number density and aspect ratio, weakens the strengthening effect, and leads to a significant decrease in alloy performance, which seriously restricts the application of Al-Cu alloy in high temperature environments.

[0003] At present, there are two main methods to improve the high-temperature properties of Al-Cu alloys: 1) Introducing a large volume fraction of thermally stable second phases into the alloy, such as ceramic phases such as Al2O3, TiC, TiB2 and trialuminum compounds such as Al3Sc, Al3Zr, Al3Ce. These second phases will not coarsen or dissolve during high-temperature thermal exposure, and can replace the original θ'-Al2Cu phase with poor stability to improve the high-temperature stability of Al-Cu alloys; 2) Introducing elements that diffuse slowly in the Al matrix, such as Sc, Zr, Mn, etc., and segregating them to the θ'-Al2Cu / α-Al interface, thereby reducing the θ'-Al2Cu phase interface energy, weakening the main driving force of Ostwald ripening, and reducing the θ'-Al2Cu coarsening rate and improving its own thermal stability. However, the introduced second phase can only play an effective strengthening effect at a larger volume fraction. The ceramic phase will inevitably reduce the plasticity of the alloy itself due to its high mismatch with the Al matrix. The precipitation of aluminum compounds and the segregation of elements such as Sc, Zr, and Mn on the surface of the θ'-Al2Cu phase often require a higher treatment temperature (>250°C), while the peak aging temperature of Al-Cu alloy is relatively low (<200°C), which will cause a mismatch between the thermal stabilization treatment temperature and the aging strengthening temperature of the Al-Cu alloy itself, which will improve the high-temperature performance of the alloy while bringing the risk of reduced room temperature performance. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide an Al-Cu alloy with improved room temperature and high temperature performance and a preparation method thereof, so as to solve the problem that the Al-Cu alloy in the prior art is difficult to meet both room temperature performance and high temperature performance.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions: An Al-Cu alloy with improved room temperature and high temperature properties, comprising, by mass fraction, 3-7% Cu, 0.3-0.6% X, 0.25-0.6% Z, 0.1-0.4% Q, and the remainder being Al element; X is Cr, Mn, or Cr and Mn; Z is Sc, Zr, or Sc and Zr; and Q is Sn, Cd, or In.

[0006] A further improvement of the present invention is: Preferably, the composition includes, by mass fraction, 4.7% Cu, 0.4% Cr, 0.3% Zr, 0.2% Cd, and the balance is Al.

[0007] A method for preparing the Al-Cu alloy with improved room temperature and high temperature performance comprises the following steps: Step 1, weighing and mixing raw materials, and placing the raw materials in a smelting furnace for smelting; the raw materials include Al alloy blocks, Cu alloys, X alloys, Q alloys, and Z alloys; Step 2, solidifying the molten alloy to obtain a solidified body; Step 3, the solidified body is subjected to solution treatment, water cooling, aging and water cooling in sequence to obtain an Al-Cu alloy.

[0008] Preferably, in step 1, the purity of the Al alloy block is ≥99.99%, and the purity of the Cu alloy powder, X alloy, Q alloy and Z alloy are all ≥99%.

[0009] Preferably, in step 1, the Cu alloy, X alloy, Q alloy and Z alloy are all powders; the particle size of the Cu alloy powder is 70-180 μm, and the particle sizes of the X alloy powder, Q alloy powder and Z alloy powder are all 110-180 μm.

[0010] Preferably, in step 1, the heating process is divided into three stages.

[0011] Preferably, the heating temperature in the first stage is 700-750°C, the standing time is 0.5-1h, and the heating temperature in the second stage is 700-800°C, the standing time is 1-2h.

[0012] Preferably, the heating temperature in the third stage is 700-800°C and the standing time is 1-2 h.

[0013] Preferably, in step 3, the solution temperature is 530-540°, and the solution time is 2-5 h.

[0014] Preferably, the aging temperature is 170-180°C and the aging time is 8-12h.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a microalloying method for improving the room-temperature and high-temperature properties of Al-Cu alloys at the same time. In this method, by introducing Z (Z=Sc or / and Zr) elements, Al3Z heterogeneous cores are formed during the solidification process to achieve grain refinement; by introducing Q (Q=Sn, Cd or In) elements, the formation of Cu-Q-vacancy clusters is promoted during the aging stage, the precipitation of θ'-Al2Cu phase is enhanced, and its size, distribution uniformity and precipitation number density are optimized. This design effectively improves the room-temperature properties of the alloy and significantly enhances the high-temperature properties at the initial stage of thermal exposure. In addition, the Q element further promotes the formation of X-Cu-vacancy clusters during the aging process, increases the enrichment of the X element in the θ'-Al2Cu phase, and improves its high-temperature stability during the coarsening process of θ'-Al2Cu through the solute partitioning effect. In the later stage of thermal exposure, X and Z diffuse and enrich to the coherent and semi-coherent interfaces of the θ'-Al2Cu phase, respectively, reducing the interface energy and inhibiting the coarsening driving force, forming a "sequential thermal stabilization" effect. This innovative microalloying strategy aims to simultaneously improve the room temperature and high temperature mechanical properties of Al-Cu alloys, and further broaden the application potential of Al-Cu alloys in aerospace and other fields by significantly improving their strength and stability under different temperature conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 It is the inverse pole figure of the grain structure of the microalloyed alloy in the cast state; Figure 2 This is the scanning electron microscope image of the microalloyed alloy in T6 treatment state; Figure 3 This is the transmission electron microscope image of the microalloyed alloy in the T6 treatment state; Figure 4 The transmission electron microscope image of the θ'-Al2Cu phase of the microalloyed alloy treated with T6 after heat exposure at 250℃ for 40h and the corresponding composition surface scanning result; Figure 5 Comparison of hardness between microalloyed alloy and Al-4Cu alloy after T6 treatment and 250℃ heat exposure for different time DETAILED DESCRIPTION The present invention is further described in detail below in conjunction with the accompanying drawings: In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0017] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0018] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0019] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0020] The first aspect of the present invention discloses an Al-Cu alloy with improved room temperature and high temperature performance. The element composition and mass percentage of the aluminum alloy after microalloying are as follows: Cu: 3-7%, X (X=Cr and / or Mn): 0.3-0.6%, Z (Z=Sc and / or Zr): 0.25-0.6%, Q (Q=Sn, Cd or In): 0.1-0.4%, and the rest is Al element.

[0021] As a preferred solution, the Al-Cu alloy composition is 4.7% Cu, 0.4% Cr, 0.3% Zr, 0.2% Cd, and the balance is Al, in terms of mass fraction. The present invention forms an Al3Z heterogeneous core during the solidification process by introducing Z (Z=Sc and / or Zr) elements, thereby refining the grain structure. By introducing Q (Q=Sn, Cd or In) elements, the formation of Cu-Q-vacancy clusters is promoted during the aging stage, thereby promoting the precipitation of the θ'-Al2Cu phase, and regulating the size, distribution uniformity and precipitation number density of the θ'-Al2Cu phase. The two work together to not only effectively improve the room temperature performance of the alloy, but also significantly enhance the high temperature performance of the alloy at the initial stage of thermal exposure (i.e., the stage where the alloy is initially coarsened under a high temperature environment). At the same time, the Q element can also promote the formation of X-Cu-vacancy clusters during the aging process, thereby increasing the enrichment of the X element in the θ'-Al2Cu phase. Since X is thermodynamically more inclined to segregate at the θ'-Al2Cu phase interface, during the coarsening process of the θ'-Al2Cu phase, X in the Al matrix and θ'-Al2Cu phase diffuses to the interface, which plays a solute partitioning effect, further enhancing the stability and high-temperature performance of the alloy at the initial stage of high-temperature thermal exposure. During the subsequent thermal exposure process, X and Z diffuse to the coherent and semi-coherent interfaces of the θ'-Al2Cu phase, respectively, and effectively inhibit the increase of the length and thickness of the θ'-Al2Cu phase by reducing the driving force of the θ'-Al2Cu coarsening and the solute drag to form a thermal stabilization effect. This "sequential thermal stabilization" effect does not require high-temperature thermal stabilization treatment. Through the common T6 heat treatment, the high-temperature performance of the Al-Cu alloy can be effectively improved while improving the room-temperature performance.

[0022] A second aspect of the present invention discloses a method for preparing an Al-Cu alloy having improved room temperature and high temperature properties, the method comprising the following steps: Step 1, weighing raw materials according to the set raw material percentage, placing the raw materials in a smelting furnace for smelting to obtain a molten alloy; Step 2, pouring the molten alloy into a mold to obtain a solidified body; Step 3, heat-treating the solidified body to obtain an Al-Cu alloy having a composition and a microstructure that meet the requirements; Step 4: Process the Al-Cu alloy into alloy blocks according to size requirements, or into wire or powder to be used for additive manufacturing.

[0023] In some embodiments of the present invention, in step 1, the smelting furnace used is a resistance smelting furnace.

[0024] In some embodiments of the present invention, in step 1, the raw material is a pure Al alloy block with a purity of 99.99%; the purity of the Cu alloy powder, X alloy, Q alloy and Z alloy are all ≥99%.

[0025] In some exemplary cases, pure Cu alloy powder with a purity of 99% and a particle size of 70~180 μm; pure Cr alloy powder with a purity of 99% and a particle size of 110~180 μm; pure Mn alloy powder with a purity of 99% and a particle size of 110~180 μm; pure Zr alloy powder with a purity of 99% and a particle size of 110~180 μm; pure Sc alloy powder with a purity of 99% and a particle size of 110~180 μm; pure Sn alloy powder with a purity of 99% and a particle size of 110~180 μm; pure Cd alloy powder with a purity of 99% and a particle size of 110~180 μm; and pure In alloy powder with a purity of 99% and a particle size of 110~180 μm are used.

[0026] In some embodiments of the present invention, during the heating process, the temperature is heated to 700-750°C to melt, and the mixture is allowed to stand for 0.5-1h, and the melt is stirred using a graphite stirring rod; the temperature is raised to 800-900°C, and the mixture is allowed to stand for 1-3h, and stirred evenly; the temperature is lowered to 700-800°C, and the mixture is allowed to stand for 1-2h, and stirred evenly.

[0027] In some embodiments of the present invention, in step 3, the heat treatment process used is: solution treatment at 530-540°C for 2-5 h, followed by water cooling to 25°C; aging at 170-180°C for 8-12 h, followed by water cooling to 25°C. Combining this part of the heat treatment process, it can be seen that the present invention uses conventional heat treatment parameters. During the casting solidification process, Z atoms form Al3Z particles, which act as heterogeneous cores to promote the refinement of α-Al grains. Subsequently, during the T6 heat treatment process (including solution treatment and artificial aging), the Q element, due to its high vacancy binding energy, can combine with vacancies and Cu atoms at the beginning of aging to form Q-vacancy-Cu clusters, thereby promoting the precipitation of θ'-Al2Cu phase, reducing its size and increasing its size uniformity, and increasing the number density of precipitation. The refined grains and the high-density small-sized θ'-Al2Cu phase work together to effectively improve the room temperature mechanical properties of the alloy.

[0028] In the early stage of thermal exposure (i.e., the stage when the alloy is initially coarsened under high temperature), the θ'-Al2Cu phase with a more uniform size distribution after microalloying can effectively reduce the driving force for phase coarsening caused by size difference and reduce the coarsening rate of the θ'-Al2Cu phase. At the same time, the Al3Zr particles produced by solidification have excellent thermal stability. The synergistic effect of the two can effectively improve the high-temperature performance of the alloy in the early stage of thermal exposure. Furthermore, both Z atoms and X atoms have strong segregation energy at the θ'-Al2Cu phase interface. During the thermal exposure process, Z and X atoms dissolved in the Al matrix will segregate to the θ'-Al2Cu phase interface driven by the segregation energy, reduce the interfacial energy of these interfaces, and reduce the coarsening driving force. At the same time, due to the slow diffusion rate of Z and X atoms in the Al matrix, they can effectively hinder the diffusion of Cu atoms to the θ'-Al2Cu phase after segregation, play a solute drag effect, further reduce the phase coarsening rate, and improve the high-temperature performance of the alloy in the later stage of thermal exposure.

[0029] The following is further described in conjunction with specific embodiments: Example 1 Step 1: Alloy smelting 1) The melting furnace used in this case is a resistance melting furnace, and the raw materials are pure Al alloy blocks with a purity of 99.99%; pure Cu alloy powder with a purity of 99% and a particle size of 70~180 μm; pure Cr alloy powder with a purity of 99% and a particle size of 110~180 μm; pure Zr alloy powder with a purity of 99% and a particle size of 110~180 μm; pure Cd alloy powder with a purity of 99% and a particle size of 110~180 μm.

[0030] 2) Place the above raw materials in an electric arc furnace, heat to 700°C to melt, let stand for 1 hour, and stir the melt with a graphite stirring rod; heat to 900°C, let stand for 2 hours, and stir evenly; cool to 800°C, let stand for 1 hour, and stir evenly; obtain a molten alloy liquid; Step 2: pour the molten alloy into a cold stainless steel mold.

[0031] The final composition of the microalloyed alloy detected by ICP (mass ratio): Al-4.7Cu-0.4Cr-0.3Zr-0.2Cd Step 3, heat treatment process The heat treatment process used is: solution treatment at 535°C for 3 h, followed by water cooling to 25°C; aging at 175°C for 10 h, followed by water cooling to 25°C, to prepare the Al-Cu alloy.

[0032] See also Figure 1 , Figure 1The inverse pole figure of the grain structure of the cast Al-4.7Cu-0.4Cr-0.5Zr-0.2Cd alloy shows that the diameter of the α-Al grains is 21.4 ± 7.8 μm, which is much smaller than the grain size of conventional cast Al-Cu alloys (>100 μm). Figure 2 This is the scanning electron microscope image of the microalloyed alloy after T6 treatment. It can be observed that a large number of Al3Zr particles are distributed on the Al matrix. Figure 3 The transmission electron microscope image shows that the bright white needle-shaped precipitates are θ'-Al2Cu phases, and the bright white spherical precipitates are Cd-rich phases. Statistics show that the average diameter and thickness of the θ'-Al2Cu phase are 48.2 ± 12.3 nm and 1.9 ± 0.6 nm, respectively, which are significantly smaller than the typical size of the θ'-Al2Cu phase in traditional Al-Cu alloys (diameter>200 nm, thickness>10nm). In addition, the ratios of the half-peak width of the diameter and thickness of the θ'-Al2Cu phase to the corresponding average values ​​are 0.76 and 0.65, respectively, indicating that the size distribution range of the θ'-Al2Cu phase is narrow, which helps to improve the thermal stability of the alloy microstructure. Figure 4 The transmission electron microscope image of the θ'-Al2Cu phase of the microalloyed alloy after thermal exposure at 250°C for 40 h and the corresponding composition surface scanning results show that Cr and Zr are significantly segregated at the θ'-Al2Cu phase interface, which helps to inhibit the coarsening of the precipitated phase. Figure 5 The hardness changes of microalloyed alloy and unalloyed Al-4Cu alloy after T6 treatment and under different conditions of heat exposure at 250°C are shown. The experimental results show that the initial hardness of the alloy after microalloying increases from 102.5 ± 1.4 Hv to 127.8 ± 1.4 Hv, an increase of 24.7%. After 70 hours of heat exposure at 250°C, the hardness of Al-4Cu alloy and microalloyed alloy is 76.7 ± 0.1 Hv and 115.6 ± 0.6Hv, respectively, which is equivalent to 74.8% and 90.5% of their respective T6 state hardness. This shows that microalloying treatment significantly improves the hardness retention rate of the alloy under high temperature conditions and enhances thermal stability, thereby giving the alloy better high temperature performance.

[0033] Example 2 Step 1: Alloy smelting 1) The melting furnace used in this case is a resistance melting furnace, and the raw materials are pure Al alloy blocks with a purity of 99.99%; pure Cu alloy powder with a purity of 99% and a particle size of 70~180 μm; pure Mn alloy powder with a purity of 99% and a particle size of 110~180 μm; pure Sc alloy powder with a purity of 99% and a particle size of 110~180 μm; and pure Sn alloy powder with a purity of 99% and a particle size of 110~180 μm.

[0034] 2) Place the above raw materials in an electric arc furnace, heat to 720°C to melt, let stand for 0.8 h, and stir the melt with a graphite stirring rod; heat to 800°C, let stand for 3 h, and stir evenly; cool to 700°C, let stand for 2 h, and stir evenly; obtain a molten alloy liquid; Step 2: pour the molten alloy into a cold stainless steel mold.

[0035] The final composition of the microalloyed alloy detected by ICP is (mass ratio): Al-6Cu-0.5Mn-0.25Sc-0.3Sn Step 3, heat treatment process The heat treatment process used is: solution treatment at 530°C for 2 h, followed by water cooling to 25°C; aging at 180°C for 8 h, followed by water cooling to 25°C.

[0036] Example 3 Step 1: Alloy smelting 1) The melting furnace used in this case is a resistance melting furnace, and the raw materials are pure Al alloy blocks with a purity of 99.99%; pure Cu alloy powder with a purity of 99% and a particle size of 70~180 μm; pure Cr alloy powder with a purity of 99% and a particle size of 110~180 μm; pure Mn alloy powder with a purity of 99% and a particle size of 110~180 μm; pure Zr alloy powder with a purity of 99% and a particle size of 110~180 μm, and pure In alloy powder with a purity of 99% and a particle size of 110~180 μm.

[0037] 2) Place the above raw materials in an electric arc furnace, heat to 730°C to melt, let stand for 1 hour, and stir the melt with a graphite stirring rod; heat to 850°C, let stand for 2 hours, and stir evenly; cool to 750°C, let stand for 1 hour, and stir evenly; obtain a molten alloy liquid; Step 2: pour the molten alloy into a cold stainless steel mold.

[0038] The final composition of the microalloyed alloy determined by ICP is (mass ratio): Al-3Cu-0.15Cr-0.3Mn-0.5Zr-0.1In.

[0039] Step 3, heat treatment process The heat treatment process used is: solution treatment at 540°C for 5 h, followed by water cooling to 25°C; aging at 170°C for 12 h, followed by water cooling to 25°C.

[0040] Example 4 Step 1: Alloy smelting 1) The melting furnace used in this case is a resistance melting furnace, and the raw materials are pure Al alloy blocks with a purity of 99.99%; pure Cu alloy powder with a purity of 99% and a particle size of 70~180 μm; pure Cr alloy powder with a purity of 99% and a particle size of 110~180 μm; pure Sc alloy powder with a purity of 99% and a particle size of 110~180 μm; and pure Cd alloy powder with a purity of 99% and a particle size of 110~180 μm.

[0041] 2) Place the above raw materials in an electric arc furnace, heat to 750°C to melt, let stand for 0.5 h, and stir the melt with a graphite stirring rod; heat to 900°C, let stand for 1 h, and stir evenly; cool to 800°C, let stand for 2 h, and stir evenly; obtain a molten alloy liquid; Step 2: pour the molten alloy into a cold stainless steel mold.

[0042] The final composition of the microalloyed alloy detected by ICP (mass ratio): Al-5Cu-0.3Cr-0.6Sc-0.4Cd Step 3, heat treatment process The heat treatment process used is: solution treatment at 530°C for 4 h, followed by water cooling to 25°C; aging at 175°C for 10 h, followed by water cooling to 25°C.

[0043] Example 5 Step 1: Alloy smelting 1) The melting furnace used in this case is a resistance melting furnace, and the raw materials are pure Al alloy blocks with a purity of 99.99%; pure Cu alloy powder with a purity of 99% and a particle size of 70~180 μm; pure Mn alloy powder with a purity of 99% and a particle size of 110~180 μm; pure Zr alloy powder with a purity of 99% and a particle size of 110~180 μm; pure Sc alloy powder with a purity of 99% and a particle size of 110~180 μm; and pure Sn alloy powder with a purity of 99% and a particle size of 110~180 μm.

[0044] 2) Place the above raw materials in an electric arc furnace, heat to 740°C to melt, let stand for 1 hour, and stir the melt with a graphite stirring rod; heat to 800°C, let stand for 3 hours, and stir evenly; cool to 700°C, let stand for 1 hour, and stir evenly; obtain a molten alloy liquid; Step 2: pour the molten alloy into a cold stainless steel mold.

[0045] The final composition of the microalloyed alloy detected by ICP is (mass ratio): Al-7Cu-0.6Mn-0.2Zr-0.2Sc-0.25Sn Step 3, heat treatment process The heat treatment process used is: solution treatment at 540°C for 2 h, followed by water cooling to 25°C; aging at 180°C for 9 h, followed by water cooling to 25°C.

[0046] Example 6 Step 1: Alloy smelting 1) The melting furnace used in this case is a resistance melting furnace, and the raw materials are pure Al alloy blocks with a purity of 99.99%; pure Cu alloy powder with a purity of 99% and a particle size of 70~180 μm; pure Cr alloy powder with a purity of 99% and a particle size of 110~180 μm; pure Zr alloy powder with a purity of 99% and a particle size of 110~180 μm; pure Sc alloy powder with a purity of 99% and a particle size of 110~180 μm; pure In alloy powder with a purity of 99% and a particle size of 110~180 μm.

[0047] 2) Place the above raw materials in an electric arc furnace, heat to 740°C to melt, let stand for 1 hour, and stir the melt with a graphite stirring rod; heat to 850°C, let stand for 1 hour, and stir evenly; cool to 750°C, let stand for 2 hours, and stir evenly; obtain a molten alloy liquid; Step 2: pour the molten alloy into a cold stainless steel mold.

[0048] The final composition of the microalloyed alloy determined by ICP is (mass ratio): Al-4Cu-0.35Cr-0.25Zr-0.2Sc-0.35In.

[0049] Step 3, heat treatment process The heat treatment process used is: solution treatment at 535°C for 5 h, followed by water cooling to 25°C; aging at 170°C for 11 h, followed by water cooling to 25°C.

[0050] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. An Al-Cu alloy with improved room temperature and high temperature performance, characterized in that: The invention comprises, by mass fraction, 3-7% Cu, 0.3-0.6% X, 0.25-0.6% Z, 0.1-0.4% Q, and the balance Al element; X is Cr, Mn, or Cr and Mn; Z is Sc, Zr, or Sc and Zr; and Q is Sn, Cd, or In.

2. The Al-Cu alloy with improved room temperature and high temperature performance according to claim 1, characterized in that: Calculated by mass fraction, it includes: 4.7% Cu, 0.4% Cr, 0.3% Zr, 0.2% Cd, and the balance is Al.

3. A method for preparing an Al-Cu alloy with improved room temperature and high temperature performance as claimed in claim 1, characterized in that: The following steps are involved: Step 1, weighing and mixing raw materials, and placing the raw materials in a smelting furnace for smelting; the raw materials include Al alloy blocks, Cu alloys, X alloys, Q alloys, and Z alloys; Step 2, solidifying the molten alloy to obtain a solidified body; Step 3, the solidified body is subjected to solution treatment, water cooling, aging and water cooling in sequence to obtain an Al-Cu alloy.

4. The method for preparing an Al-Cu alloy with improved room temperature and high temperature performance according to claim 3, characterized in that: In step 1, the purity of the Al alloy block is ≥99.99%, and the purity of the Cu alloy powder, X alloy, Q alloy and Z alloy are all ≥99%.

5. The method for preparing an Al-Cu alloy with improved room temperature and high temperature performances according to claim 3, characterized in that: In step 1, the Cu alloy, X alloy, Q alloy and Z alloy are all powders; the particle size of the Cu alloy powder is 70-180 μm, and the particle sizes of the X alloy powder, Q alloy powder and Z alloy powder are all 110-180 μm.

6. The method for preparing an Al-Cu alloy with improved room temperature and high temperature performances according to claim 3, characterized in that: In step 1, the heating process is divided into three stages.

7. The method for preparing an Al-Cu alloy with improved room temperature and high temperature performances according to claim 6, characterized in that: The heating temperature in the first stage is 700-750°C, and the standing time is 0.5~1h. The heating temperature in the second stage is 700~800°C, and the standing time is 1~2h.

8. The method for preparing an Al-Cu alloy with improved room temperature and high temperature performances according to claim 6, characterized in that: The heating temperature in the third stage is 700~800°C and the standing time is 1~2 h.

9. The method for preparing an Al-Cu alloy with improved room temperature and high temperature performances according to claim 3, characterized in that: In step 3, the solution temperature is 530-540°, and the solution time is 2-5 h.

10. The method for preparing an Al-Cu alloy with improved room temperature and high temperature performances according to claim 3, characterized in that: The aging temperature is 170~180°C, and the aging time is 8~12h.